Gênero e cárcere: As Representações Sociais de mulheres sobre as visitas íntimas em penitenciárias femininas - BEATRYZ ANDRADE LIRA (2023)
Academic studies and social movements reveal the demands of the incarcerated female population in Brazil and tell us what happens between walls and bars, which, most of the time, are events invisible to a large part of society. Aiming to understand the elements that involve women, sexuality, incarceration, and gender relations, this study aims to analyze the Social Representations (SR) of women in a regime of deprivation of liberty about intimate visits in the female prison. The study is based on the Theory of Social Representations (TSR), developed by Serge Moscovici and gender studies, having as its axis the category of gender analysis. Methodologically, it is a descriptive and qualitative research. The collection of information was carried out through individual interviews following a semi-structured script and the use of the word evocation technique as a projective strategy, seeking to reveal the SR of the research participants, with the inductive/stimulus terms: prison, detainee, intimate visit, visit, and myself. For the treatment of information acquired in interviews and the word evocation technique, the Content Analysis technique of Laurence Bardin was used, for the organization of nuclei and categories of analysis, aiming to analyze the meaning of communications in the description of the manifest contents collected. The interviews were conducted with 12 (twelve) women who have already experienced deprivation of liberty in a closed regime. The location of the participants occurred from an active search on social networks, indications of social movements, pastoral, family movements, and the Female Penal Establishment. The contents were organized into three thematic axes: Sexuality of incarcerated women, Closed regime and expressed feelings, and Experienced violence. These axes made it possible to visualize the SR of the women participating in the study about the intimate visit. In this way, it was possible to identify that women in a regime of deprivation of liberty live an ambiguity of feelings about sexuality, which, from the SR, emerged, mainly, as shame, suffering, denial/blocking of sexuality, and frustration. Family relations revealed the importance of family support and the maternal function as a tool for overcoming, manifesting the confrontation between hope and reality, structural barriers in the female universe as well as the stigmatization present in prison and the lag in public policies. Regarding the violence experienced, the double punishment from intimacy, the asymmetry between female and male present in the regime of deprivation of liberty, and humiliation were revealed, which manifest from the "punishment of the house" with the female submission on the margin of crimes and the cycle of prison in the female universe. Keywords: Woman. Penitentiary. Gender. Social Representations.